Fibromyalgia: heterogeneity in personality and psychopathology and its implications - Gonzalez, B.; Novo, R.; Sousa Ferreira, A. (Psychology, Health and Medicine, 2020)
The fibromyalgia syndrome (FM) is a chronic widespread pain condition whose etiology remains unknown and no treatment has satisfactory levels of success. A meta-analysis has identified a distinct Minnesota Multiphasic Personality Inventory-2 (MMPI-2) clinical profile between FM female patients and healthy controls, and differences between FM and other chronic pain condition with clear etiology have also been found. However, heterogeneity in this population has been suggested in several studies. We aim to assess clinical aspects in FM patients, based on personality psychopathology characteristics, in order to explore heterogeneity and the existence of core common aspects. In this cross-sectional study, a relatively homogeneous sample of 56 female FM patients (Mage = 45.95, SDage = 9.39) was assessed through MMPI-2. A K-Means cluster analysis identified two clusters, one (n = 24) with clinically significant levels in Negative Emotionality and Introversion scales. Subsequent MANOVAs identified important features of this cluster on several MMPI-2 dimensions. Moreover, several dimensions are clinically elevated in both clusters. In conclusion, the combination of psychopathological negative emotionality, interpersonal isolation, and low hedonic capacity, in a group of patients, has implications for the daily living and treatment of FM patients, and several core aspects of FM need to be addressed.